Identifying Causes of Temporal Changes in Acropora cervicornis Populations and the Potential for Recovery - Goergen, Elizabeth A.; Moulding, Alison L.; Walker, Brian K.; Gilliam, David S. (Frontiers in Marine Science, 2019)
Corals, specifically the Atlantic staghorn coral, Acropora cervicornis, have become more vulnerable to disturbance events such as storms and disease and predation outbreaks. Since its population declines due to a wide spread disease event in the early 1980s, limited long-term monitoring studies describing the impact of current threats and potential recovery have been completed. The aim of this study was to document the impacts of environmental (tropical storms, increased wind) and biological (disease and predation) threats on A. cervicornis to further understand its dynamics and potential for recovery. Two high-density A. cervicornis patches (greater than 1 hectare each) were surveyed tri-annually (winter, summer, fall) from 2008-2016. Acropora cervicornis percent cover, canopy height, census of individuals (fragments, colonies and masses), and prevalence and occurrence of disease, predation, and bleaching were evaluated within permanent 3.5 m radial plots. Temporal variability was observed in mean percent live cover at both patches and resulted in an overall loss of tissue. Frequent disturbances such as tropical storms, hurricanes, and disease events caused increased, prolonged, and widespread mortality. Periods void of disturbance allowed for recovery and growth. Prevalence and occurrence of disease and predation were highly variable between monitoring events. They were also found to be significantly higher on masses (individuals ≥ 1.5 m) than on colonies and during summer surveys. These data indicate that substantial length of time between major disturbance events are necessary for recovery and growth of this species. The implication from these results is that given the current rates of growth, recruitment, and storm frequency, natural species recovery is unlikely unless larger scale issues are addressed such as climate change and ocean warming, which could reduce the intensity and frequency of disease and predation.